Proclus and the Intelligible-Intellectual Roots of Mathematical Theology - Maggi, Claudia (Peitho. Examina Antiqua, 2025)
The purpose of my paper is to investigate some aspects of Proclus’ foundation of the theological role of mathematics. In the first section, I briefly discuss the question of the foundation project of mathematics in Plato, as I believe it is also from the dialogues that Proclus derives the crucial status of mathematical entities in the ascent of the soul. In the second part, after presenting the four ways that Proclus recognizes as theological and pointing out that mathematics is made part of theology through images, I analyze in particular the theological power of two geometrical images, that of the divided line and that of the circle. Lastly, the third section firstly emphasizes that the theological status of mathematics finds its ontological validation in the Proclean theory of mathematical entities as intermediates. Then, it focuses on the intelligible-intellectual roots of the intermediates themselves, which ensure that the soul’s ascent is surely directed toward the highest realities.